Advanced Practice Physiotherapists and the implementation of the JIGSAW-E model for the management of osteoarthritis in Scottish primary care settings: a qualitative case study. (December 2022) - Frost, H.; Tooman, T.; Cowie, J.; Gillespie, N.; Ackerman, P.; Krievs, E.; Dziedzic, K.
Abstract: Objective: To explore the acceptability, barriers and enablers of NICE guidelines for osteoarthritis in the Scottish primary care setting using the Joint Implementation of Guidelines for Osteoarthritis in Western Europe (JIGSAW-E) model and investigate the role of Advanced Physiotherapy Practitioners (APPs) in providing evidence-based care. Design: A qualitative case study comprised of semi-structured interviews followed by a workshop with participants. Setting: 10 Scottish primary care practices. Participants: Six general practitioners (GPs) and eight APPs were interviewed. Twenty-three practitioners attended the workshop including 22 physiotherapists and one GP. Results: While both GPs and APPs recognised the need to improve and standardise osteoarthritis care delivery, this study found that APPs were better situated to implement the evidence-based model. Barriers to implementation included lack of time for training, limited appointment time for GPs to consult and discuss medication use with patients, limitation of disease specific guidelines for patients with complex multimorbidity, and system-based barriers such as electronic data collection and high staff turnover. The key enabler was practitioners' motivation to provide optimal, standardised quality care for osteoarthritis. To increase acceptance, ownership and usability for both practitioners and patients, the JIGSAW-E model materials required adaptation to the local context. Conclusion: This study provides evidence that the JIGSAW-E model is acceptable in Scottish primary care. Furthermore, the evolving roles of GPs and APPs within multidisciplinary primary care teams provides a platform to implement the JIGSAW-E model, where APPs are well placed to provide leadership and training in the delivery of evidence-based care for osteoarthritis. Contribution of the paper: This paper provides evidence of the acceptability by Advanced Physiotherapy Practitioners to implement the JIGSAW-E models of care for osteoarthritis in Scottish primary care. It supports the large body of previous research on the implementation of the JIGSAW-E model across England and Europe that aims to provide optimal care for people with osteoarthritis. The main findings highlight that Advanced Physiotherapy Practitioners have the motivation and capability to lead the development of evidence-based care for people with osteoarthritis within the framework of a multi-professional primary care team.